Biogeographic patterns of base‐rich fen vegetation across Europe. Issue 2 (15th October 2013) - Jiménez‐Alfaro, Borja; Hájek, Michal; Ejrnaes, Rasmus; Rodwell, John; Pawlikowski, Paweł; Weeda, Eddy J.; Laitinen, Jarmo; Moen, Absjørn; Bergamini, Ariel; Aunina, Liene; Sekulová, Lucia; Tahvanainen, Teemu; et al.
Abstract Questions What is the distribution of base‐rich fen vegetation and the specialist species along European biogeographic regions? How do the gradients in species composition correlate to geography and climate at continental scale? What are the implications of such patterns for the classification of these habitats? Location Fifteen countries of Central, Western and Northern Europe. Methods We compiled a vegetation plot database of base‐rich fens and related communities including vascular plants and bryophytes. The initial data set with 6943 plots was filtered according to the presence of specialists using discriminant analysis. We used DCA to analyse the correlation of species composition with geography and climate, and kriging interpolation for mapping gradients in the study area. Modified TWINSPAN was used to detect major vegetation groups. The results of the whole data set (plot size 1–100 m2) were compared with those obtained from two subsets with plots of 1–5 m2 and 6–30 m2. Results Most of the specialists were distributed among all the biogeographic regions, but many were more represented in the Alpine than in the Atlantic, Boreal and Continental regions. Variation in species composition was mainly correlated to temperature, precipitation and latitude in the three data sets, showing a major gradient from (1) alpine belt fens characterized by spring species to (2) small sedge fens mainly distributed in mountain regions and (3) boreo‐temperate fens reflecting waterlogged conditions. Conclusions Base‐rich fen communities are widely distributed across European biogeographic regions, but the Alpine region can be considered as the compositional centre of this vegetation type. Large‐scale gradients of species composition are mainly explained by climate, while the influence of latitude is probably correlated to increasing water table in the boreo‐temperate regions. These gradients can be better understood by differentiating three major vegetation types, which should be considered when establishing classification systems of base‐rich fens in Europe.